2012
DOI: 10.1158/0008-5472.can-12-1772
|View full text |Cite
|
Sign up to set email alerts
|

The V-ATPase-Inhibitor Archazolid Abrogates Tumor Metastasis via Inhibition of Endocytic Activation of the Rho-GTPase Rac1

Abstract: The abundance of the multimeric vacuolar ATP-dependent proton pump, V-ATPase, on the plasma membrane of tumor cells correlates with the invasiveness of the tumor cell, suggesting the involvement of V-ATPase in tumor metastasis. V-ATPase is hypothesized to create a proton efflux leading to an acidic pericellular microenvironment that promotes the activity of proinvasive proteases. An alternative, not yet explored possibility is that V-ATPase regulates the signaling machinery responsible for tumor cell migration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
96
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 44 publications
4
96
0
Order By: Relevance
“…For example, in a 4T1‐Luc mouse breast cancer xenograft model, archazolid treatment inhibited lung metastasis at a concentration (1 mg/kg i.v.) which did not cause signs of obvious toxicity 64. Similar results were obtained using baf‐A1, in which treatment led to the reduction of average tumor volume by 50% in MCF‐7 and MDA‐MB‐231 xenograft mouse models.…”
Section: V‐atpase As a Potential Cancer Therapeutic Targetsupporting
confidence: 74%
“…For example, in a 4T1‐Luc mouse breast cancer xenograft model, archazolid treatment inhibited lung metastasis at a concentration (1 mg/kg i.v.) which did not cause signs of obvious toxicity 64. Similar results were obtained using baf‐A1, in which treatment led to the reduction of average tumor volume by 50% in MCF‐7 and MDA‐MB‐231 xenograft mouse models.…”
Section: V‐atpase As a Potential Cancer Therapeutic Targetsupporting
confidence: 74%
“…Although a number of studies have implicated the V-ATPase in tumor cell invasion, the mechanisms by which the pump is involved in this process have not been elucidated (17)(18)(19)(20)(21)(22)(23)(24). Several reports have identified a correlation between cancer cell invasiveness and V-ATPase localization to the plasma mem- A, untransfected control and c-V5-transfected cells were incubated in the absence or presence of a monoclonal antibody against V5 and then loaded with SNARF-1.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has found that subunit C interacts with F-actin at the plasma membrane of invasive breast cancer cells and that loss of this subunit disrupts actin arrangement in these cells (54). Moreover, inhibiting V-ATPases with archazolids has been found to impair plasma membrane localization of EGFR and Rac1 in SKBR3 breast cancer cells, a critical process for cell migration (23). It has also been suggested that plasma membrane V-ATPases present in the leading edge of microvascular endothelial cells promote migration through a local increase in cytosolic pH, which facilitates actin polymerization (4,55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of metastatic cells with the V-ATPase inhibitor archazolid limited leading edge localization of the epidermal growth factor receptor and blocked endocytic activation of Rac1, a member of the Rho family of small GTPases with known functions in cell migration (40). Inhibition of V-ATPases with bafilomycin or through siRNA silencing prevented peripheral localization of Rab27 secretory vesicles and blocked heat shock protein 90␣ secretion (41).…”
Section: Discussionmentioning
confidence: 99%